Song, Poetry and Images in Writing: Sami Literature - Gaski, Harald (Nordlit, 2011)
The article is an overview of Sami literature, past and present, with a specific emphasis on the connection between tradition and innovation, in which literature is regarded in a broader sense than only limited to the written word. Thus the relationship between the traditional epic yoik songs and contemporary poetry is being dealt with, as is the multimedia approach that several Sami artists have chosen for their creative expression. It is almost more the rule than an exemption that Sami artists express themselves through the use of more than only one medium. Through the introduction to Sami literature, the reader also gets acquainted with the history and the culture of the Sami, who are the indigenous people of the northern regions of Scandinavia, Finland and the Kola peninsula in Russia.